(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article is devoted to the problems of combating terrorism and its threat to society and the state.The specific formation of terrorist groups, the reasons for their appearance and the goals set by these organizations are considered.Ultimately, the article suggests several options for strengthening the fight against terrorism around the world.